Perbandingan Produktivitas dan Kualitas Tunggul Kegiatan Penebangan Menggunakan Attachment Shearhead dan Attachment Harvester pada Waktu yang Berbeda di PT. RAPP: Comparison Of Productivity and Quality of Logging Activities Using Shearhead and Harvester Attachmentsa at Different Times at PT. RAPP - Valentino S, Edward Jhonatan; Falah, Muhammad Darul; Nugraha, Nanda Satya (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The use of wood harvesting equipment really helps companies to achieve their goals, which are to speed up the process of implementing work, carrying out types of work that cannot be done by human labor, and this is done for reasons of the sustainability of logging operations, labor limitations, safety and quality factors of logging results. Therefore, in order to achieve the goal, it is necessary to select tools that are appropriate, quality and in accordance with the working conditions. The selection of inappropriate tools can result in the failure to achieve the expected goals and can cause damage to the tools and damage to the area. In the process of logging carried out at PT. RAPP on a fully mechanical system uses different logging tools. Each tool in logging activities has its own disadvantages and advantages. Therefore, it is necessary to conduct research on the comparison of productivity and quality of stump from logging using an excavator attachmant shearhead and an excavator attachmant harvester on Eucalyptus sp. Based on the results of the test analysis carried out, it was found that the average productivity of the CAT 320D excavator with a 14 in